Implementasi User Interface Pada Multimedia Interaktif Cerita Rakyat Dari Kalimantan Barat - Rochmawati, Irma; Albar, Deni (Visualita Jurnal Online Desain Komunikasi Visual, 2022)
The application of the user interface is very important for those who develop media in assessing the success of an interactive multimedia design. Ideally a media can function according to the plan and can meet the needs and desires of its users. If planning and analysis are not clear, it can cause problems that will have an impact on development activities. This study will provide an overview of the implementation of the user interface with the prototyping method in interactive multimedia development activities, with the hope of producing a prototype design as one of the first steps in a digital media development activity. The prototype is made with the aim of providing a common perception and initial understanding of the basic process of the user interface to be developed, so that there will be good communication between developers and system users. The results of this study can be used as a reference or reference for interactive multimedia design developers who have followed the prototyping steps in a structured manner, thus providing a clear process for users and observers of the science of developing interactive multimedia design.